2022
DOI: 10.3389/fonc.2022.940601
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating a prognostic nomogram for ovarian clear cell carcinoma patients: A retrospective comparison of lymph node staging schemes with competing risk analysis

Abstract: PurposeLymph node (LN) involvement is a key factor in ovarian clear cell carcinoma (OCCC) although, there several indicators can be used to define prognosis. This study examines the prognostic performances of each indicator for OCCC patients by comparing the number of lymph nodes examined (TNLE), the number of positive lymph nodes (PLN), lymph node ratio (LNR), and log odds of metastatic lymph nodes (LODDS).Methods1,300 OCCC patients who underwent lymphadenectomy between 2004 and 2015 were extracted from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…However, we can confirm that it has distinct histopathological, and molecular characteristics compared with other histologic subtypes of epithelial ovarian cancer [4,24,25]. Previous studies have established that the prognosis of advanced OCCC is far from satisfactory, even worse than that of advanced OSC [26]. This aligns with our findings, which demonstrate that survival outcomes for late-stage OCCC patients are even poorer compared to those in early-stage.…”
Section: Discussionsupporting
confidence: 90%
“…However, we can confirm that it has distinct histopathological, and molecular characteristics compared with other histologic subtypes of epithelial ovarian cancer [4,24,25]. Previous studies have established that the prognosis of advanced OCCC is far from satisfactory, even worse than that of advanced OSC [26]. This aligns with our findings, which demonstrate that survival outcomes for late-stage OCCC patients are even poorer compared to those in early-stage.…”
Section: Discussionsupporting
confidence: 90%
“…It considers both positive and negative lymph node status and has been demonstrated to be clinically valuable by many studies [ 14 17 , 21 , 25 , 26 ]. Several studies have suggested using pLN and pLNR [ 27 , 28 ]. However, the pLN is also directly limited by the eLN, and additional help is needed to avoid staging migration [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, However, this model was only internally validated and lacks external validation using cohorts from other countries to assess its performance. Similarly, Li et al [25] established a nomogram for predicting progression-free survival and overall survival in OCCC patients at a large ovarian cancer center in China. They demonstrated that their nomogram outperformed the FIGO system, but external validation will still be necessary in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been widely used as the preferred method for individualized predictions in numerous model building studies [14,25,26]. However, nomograms have limitations in time-event prediction and fail to capture the nonlinear relationships among clinical features.…”
Section: Discussionmentioning
confidence: 99%